2017
DOI: 10.1021/acsami.7b07351
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Evidence of Size-Dependent Buffering of Interfacial pH by Cation Hydrolysis during CO2 Electroreduction

Abstract: The nature of the electrolyte cation is known to affect the Faradaic efficiency and selectivity of CO electroreduction. Singh et al. (J. Am. Chem. Soc. 2016, 138, 13006-13012) recently attributed this effect to the buffering ability of cation hydrolysis at the electrical double layer. According to them, the pK of hydrolysis decreases close to the cathode due to the polarization of the solvation water molecules sandwiched between the cation's positive charge and the negative charge on the electrode surface. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
217
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(240 citation statements)
references
References 36 publications
16
217
0
2
Order By: Relevance
“…However, the local pH depends considerably on the purity of the salt used to prepare the electrolyte, and exactly opposing trends can be found if a set of alkaline‐metal carbonates of lower purity is used (see Figure , right panel), which might explain these discrepancies . Nonetheless, the highest pH increase always coincided with the lowest current densities, and vice versa …”
Section: Applications In the Electrocatalytic Reduction Of Co2mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the local pH depends considerably on the purity of the salt used to prepare the electrolyte, and exactly opposing trends can be found if a set of alkaline‐metal carbonates of lower purity is used (see Figure , right panel), which might explain these discrepancies . Nonetheless, the highest pH increase always coincided with the lowest current densities, and vice versa …”
Section: Applications In the Electrocatalytic Reduction Of Co2mentioning
confidence: 99%
“…However, this disadvantage can be turned into an advantage, and be used to determine the local pH at the interface in operando conditions. Ayemoba and Cuesta used ATR‐SEIRAS to experimentally determine the pH at the electrode‐electrolyte interface during the electroreduction of CO 2 by determining the ratio between the integrated areas of the absorption bands corresponding to CO 2 and HCO 3 − . Using gold films chemically deposited on silicon, they demonstrated that, at a given potential, the increase in the pH near the electrode surface follows the sequence Li + >Na + >K + >Cs + (Figure , left), a sequence which is exactly the inverse of that observed for the current density and selectivity for C 2 products of the CO 2 electroreduction process .…”
Section: Applications In the Electrocatalytic Reduction Of Co2mentioning
confidence: 99%
“…This mechanism is dependent on cation radius and will alter the local pH and the local CO 2 concentration near the electrode surface, ultimately altering product selectivity. Ayemoba and Cuesta have further confirmed this effect by performing surface‐enhanced infrared spectroscopy (SEIRAS) experiments on a thin‐film gold electrode …”
Section: Co2 Reduction In Aqueous Electrolytesmentioning
confidence: 99%
“…The electrolyte composition (Figure A) plays an important role on both the activity and selectivity of the CO 2 RR, as it can: i) regulate the pH and minimise the HER against CO 2 RR, ii) affect the solubility of CO 2 , iii) stabilise the reaction intermediates …”
Section: Structure Sensitivity In Co2 Reductionmentioning
confidence: 99%